Effect of mechanical pressure on the ionic conductivity of sodium dodecahydrido-closo-dodecaborate - Kristensen, Lasse; Herrmann, Gerrit; Skibsted, Jørgen; Jensen, Torben R. (ACS materials letters, 2025)
To optimize the performance of solid-state batteries, - careful control - of the material properties is essential. Solid-state batteries require - significant mechanical pressure during assembly and cycling to ensure - intimate contact and stability of the electrochemical cell. Here we - show that mechanical pressure can induce a polymorphic transition - (P21/c → Pbca) of sodium dodecahydrido-closo-dodecaborate, - Na2B12H12, which increases both the - boron dynamics and the ionic conductivity. Heating mechanically pressed - samples above 65 °C results in full conversion back to the initial - polymorph (P21/c), along - with a reduction of one order of magnitude in ionic conductivity, - which is consistent with the as-synthesized Na2B12H12. This work emphasizes the important role that postsynthesis - treatment can have on the ionic conductivity, the activation energy, - and the texture of solid electrolytes.